CORRELATION COEFFICIENT ANALYSIS BETWEEN PM2.5 CONCENTRATIONS AND SOME METEOROLOGICAL PARAMETERS IN IRAQ - Wid. M. S,; Yaseen K. Al-Timimi,; Monim H. Al-Jiboori, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to investigate of the spatial analyses of the correlation coefficient between Particulate matter PM2.5 and meteorological parameters in Iraq Using remote-sensing data and meteorological Parameters datasets for the period 2003–2020. PM2.5 is one of the primary air pollutants across the world. Quantifying interactions between meteorological conditions and PM2.5 concentrations is essential to understanding the variability of PM2.5. The spatial variations of the relationships between the annual average PM2.5, the annual average rainfall, temperature wind speed, and pressure were evaluated using the Pearson correlation coefficient model. The results indicated that there were positive correlations between PM2.5 concentrations and both temperature and wind, while there was a negative correlation with pressure. As for rainfall, there were positive correlations in some areas and negative in others. The results also showed that the most associated factor with PM2.5 is wind. it becomes clear to us that the correlations between fine particles and meteorological factors differ according to the regions, the terrain, the local climate, human and natural differences, and weather changes.